GWAS of serum ALT and AST reveals an association of SLC30A10 Thr95Ile with hypermanganesemia symptoms - Ward, Lucas D.; Tu, Ho-Chou; Quenneville, Chelsea B.; Tsour, Shira; Flynn-Carroll, Alexander O.; Parker, Margaret M.; Deaton, Aimee M.; Haslett, Patrick A. J.; Lotta, Luca A.; Verweij, Niek; Ferreira, Manuel A. R.; Baras, Aris; et al. (Nature communications, 2021)
Understanding mechanisms of hepatocellular damage may lead to new treatments for liver disease, and genome-wide association studies (GWAS) of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) serum activities have proven useful for investigating liver biology. Here we report 100 loci associating with both enzymes, using GWAS across 411,048 subjects in the UK Biobank. The rare missense variant SLC30A10 Thr95Ile (rs188273166) associates with the largest elevation of both enzymes, and this association replicates in the DiscovEHR study. SLC30A10 excretes manganese from the liver to the bile duct, and rare homozygous loss of function causes the syndrome hypermanganesemia with dystonia-1 (HMNDYT1) which involves cirrhosis. Consistent with hematological symptoms of hypermanganesemia, SLC30A10 Thr95Ile carriers have increased hematocrit and risk of iron deficiency anemia. Carriers also have increased risk of extrahepatic bile duct cancer. These results suggest that genetic variation in SLC30A10 adversely affects more individuals than patients with diagnosed HMNDYT1. Circulating liver enzymes, like alanine aminotransferase (ALT) and aspartate aminotransferase (AST), are highly heritable and predictive of disease. Here, the authors perform a genome-wide association study on ALT and AST, revealing a rare variant in SLC30A10 associated with elevated ALT and AST.